Effect of acid hydrolysis treated pineapple fiber in plasticized polylactic acid composite - Wan Osmani, Sharifah Nur Aqilah; Ali, Fathilah; Adli, Sarah Amalina (Kulliyyah of Engineering, International Islamic University Malaysia, 2018)
Pineapple leaf is a residue mainly from pineapple food industry which is causing environmental problems by its lack of proper waste disposal method. Therefore, it can be utilized as filler for the reinforcement of PLA which is brittle in nature. Treated fiber from pineapple leaf fiber (PALF) was derived through acid hydrolysis method using 64 wt% sulfuric acid at 45 ⁰C for 45 minutes. The morphological properties and chemical structure of treated PALF were determined using scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). Plasticized PLA/treated PALF was prepared by solvent casting method at 1 wt%, 3 wt%, 5 wt% and 7 wt% loading rates of acid hydrolysis treated PALF. Mechanical properties of composite were characterized through tensile test. FTIR analysis shows significant changes in the chemical properties of the raw PALF and treated PALF. SEM image reveals that acid hydrolysis treated PALF displays a rod like structure and smooth surface as the effect of hemicellulose removal. The tensile test conducted showed that composite with 1wt% acid hydrolysis treated PALF have the highest Young’s modulus at 0.46 MPa and the highest elongation at break of 310%. The findings of this research are expected to help in cost reduction of PLA composites and decrease the amount of waste accumulated in the environment due to nonbiodegradable polymer materials and the pineapple industry residues.